2022
DOI: 10.1371/journal.pone.0268258
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sanitization protocols in removing parasites in vegetables: A protocol for a systematic review with meta-analysis

Abstract: Background Parasitic contamination of vegetables is a public health problem in several countries and a challenge for food safety. With a short path from the field to the table, these foods can suffer several flaws in the good practices of production, transport and packaging which culminate in an offer of contaminated food to consumers. Therefore, this study describes a systematic review protocol with meta-analysis on evaluating the effectiveness of existing sanitation methods in removing parasites from vegetab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…It is thought that the homogenous loose nature of the large particles of sandy soils is reported to result in higher recoveries of parasites than other soil types [17]. Fresh green vegetables, particularly those consumed raw in salad dishes or barely cooked are a major source of intestinal parasite transmission and have been connected to foodborne parasitic infections in many communities throughout the world [10,39]. Contamination most likely occurs before harvest while they are in fields, either by unregulated use of contaminated raw human or animal manure, sewage sludge, infected irrigation water, or directly through unsanitary hygienic practices of humans, such as open defecation in farmlands.…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the homogenous loose nature of the large particles of sandy soils is reported to result in higher recoveries of parasites than other soil types [17]. Fresh green vegetables, particularly those consumed raw in salad dishes or barely cooked are a major source of intestinal parasite transmission and have been connected to foodborne parasitic infections in many communities throughout the world [10,39]. Contamination most likely occurs before harvest while they are in fields, either by unregulated use of contaminated raw human or animal manure, sewage sludge, infected irrigation water, or directly through unsanitary hygienic practices of humans, such as open defecation in farmlands.…”
Section: Discussionmentioning
confidence: 99%
“…This review had its protocol registered in the PROSPERO database (International Prospective Register of Systematic Reviews), with registration number CRD42020206929 and is reported following the guidelines provided in the PRISMA 2020 guide (Preferred Reporting Items for Systematic Review and Meta-Analyses) described in S1 File [10]. The protocol of this study was also published [11], detailing the methodological process of this review and promoting greater transparency in the research.…”
Section: Methodsmentioning
confidence: 99%
“…Selain memperhatikan Enam Prinsip Higiene Sanitasi Makanan, pemerintah yang berwenang dan penyedia makanan juga perlu meningkatkan kondisi dan sarana sanitasi guna sebagai upaya pencegahan cemaran parasit usus [44] . Peningkatan pengetahuan tentang praktik higiene pangan pada petani, penjual dan konsumen merupakan hal yang penting dilakukan, sebab dengan memahami praktik higiene pangan yang baik akan meningkatkan kualitas makanan [45] .…”
Section: B Sanitasi Tempat Penjualanunclassified